1999
DOI: 10.1007/bf03343573
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline: A first-choice treatment in patients with previously untreated prolactin-secreting pituitary adenoma

Abstract: Cabergoline (CAB) treatment is an effective, safe and well tolerated approach for hyperprolactinemia. We investigated the efficacy of 24-month treatment with CAB in 37 patients with previously untreated PRL-secreting pituitary adenoma and evaluated the hormonal and neuroradiological changes after the discontinuation of long-term therapy. Eleven patients with macroprolactinoma (1M/10F) and 26 with microprolactinoma (4M/22F) started treatment taking 0.25 mg CAB twice a week for 4 weeks. The dose was increased st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
5
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 26 publications
5
66
5
8
Order By: Relevance
“…Indeed, hormonal and tumoral responses were obtained in 94 and 82% of the cases respectively. This is in keeping with several previous studies (14)(15)(16)(17)(18), and an overview of the reported numbers of patients with previously untreated macroprolactinoma responding to long-term treatment with CAB is shown in Table 3.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, hormonal and tumoral responses were obtained in 94 and 82% of the cases respectively. This is in keeping with several previous studies (14)(15)(16)(17)(18), and an overview of the reported numbers of patients with previously untreated macroprolactinoma responding to long-term treatment with CAB is shown in Table 3.…”
Section: Discussionsupporting
confidence: 90%
“…Microprolactinomas are found, almost invariably, more frequently in women, while it is still questioned whether macroprolactinomas are more frequent in men. In fact, some studies have reported an equal distribution of macroprolactinomas between genders (12, 31, 32, this study), others have found higher prevalence in men (33,34) or in women (10,35). In previous studies (7,19) tumor size did not seem to be associated with the duration of symptoms; we did not analyze the duration of symptoms referable to hyperprolactinemia, and patients' age was not correlated with tumor size in either micro-or macroprolactinoma patients.…”
Section: Discussioncontrasting
confidence: 61%
“…The 50% success rate weobserved for macroprolactinomatreated with bromocriptine is lower than those of several studies (62-67%) which administered higher doses or a long-acting injectable form of bromocriptine in macroprolactinoma patients (2 1-23). On the other hand, the 85%normalization rate we found in idiopathic + microprolactinoma patients in the cabergoline group is comparable to the results of Webster et al ( 15) (83%, 88%, 93% and 96%, respectively), and the 75% normalization rate we found in macroprolactinoma patients is in accordance with the results of Ferrari et al (26), Biller et al (27) and Colao et al (28) (61%, 73% and 81%, respectively), and lower than the 100%rate reported by Cannavo et al (24), who used a higher dose of cabergoline (i.e. 3 mg/week).…”
Section: Discussionsupporting
confidence: 91%